Interaction between PLA2R1 and HLA-DQA1 Variants Associates with Anti-PLA2R Antibodies and Membranous Nephropathy - Lv, Jicheng (American Society of Nephrology, 2013)
Risk alleles at genome loci containing phospholipase A2 receptor 1 (PLA2R1) and HLA-DQA1 closely associate with idiopathic membranous nephropathy (IMN) in the European population, but it is unknown whether a similar association exists in the Chinese population and whether high-risk alleles promote the development of anti-PLA2R antibodies. Here, we genotyped 2132 Chinese individuals, including 1112 patients with IMN and 1020 healthy controls, for three single nucleotide polymorphisms (SNPs) within PLA2R1 and three SNPs within HLA genes. We also selected 71 patients, with varying genotypes, to assess for circulating anti-PLA2R antibody and for PLA2R expression in glomeruli. Three SNPs within PLA2R1 and one SNP within HLA-DQA1 strongly associated with IMN, and we noted gene–gene interactions involving these SNPs. Furthermore, these risk alleles strongly associated with the presence of anti-PLA2R antibodies and glomerular PLA2R expression. Among individuals who carried risk alleles for both genes, 73% had anti-PLA2R antibodies and 75% expressed PLA2R in glomeruli. In contrast, among individuals who carried protective genotypes of both genes, none had anti-PLA2R antibodies and glomerular expression of PLA2R was weak or absent. In conclusion, the interaction between PLA2R1 and HLA-DQA1 risk alleles associates with the development of IMN in the Chinese population. Individuals carrying risk alleles are predisposed to the generation of circulating anti-PLA2R autoantibodies, which may contribute to the development of IMN.